Determinants of foreign direct investment in Algeria - hafsa dib (Journal of Excellence for Economics and Management Research, 2025)
The aim of this study is to examine the Determinants of foreign direct investment (FDI) in Algeria using the methodology Auto Regressive Distributed Lag (ARDL), we use annual data covering 1990-2023 period.The results revealed a positive relationship between the exchange rate, trade openness, and FDI inflows in Algeria, indicating that improvements in these two factors contribute to attracting more foreign investment. Conversely, money supply had a negative impact on FDI